ANALISIS PENGARUH BAURAN PEMASARAN TERHADAP VOLUME PENJUALAN PADA RESTORAN KFC HASANUDDIN PALU - Nurhalima, Nurhalima; Effendy, Effendy; Bakhs, Rukavina (AGROTEKBIS, 2018)
This study aimed to determine the effect of the marketing mix on sale volumes at the Hasanuddin KFC restaurant in Palu. The independent variables included were product (x1), price (x2), place/location (x3), and promotion (x4) whereas the dependent variablewas the volume of sales (Y). Respondents comprised of 31 persons i.e. one manager and 30 consumers selected using a purposive sampling technique through a questionnaire completed by the respondents. Data were analyzed using a multiple linear regression analysis. The regression analysis obtained was Y = 6,582 + 0.074x1 + 0.059x2 + 0.200x3 + 0.837x4. The F test shows that the product, the price, the place of distribution channels, and the promotionsimultaneouslyinfluence the sale volume with the F-counted value of 278,228at a significant level of 0.000. The analysis also indicates that the values of the t test were 3,692 for the product, 2,857 for the price,9,775 for the distribution channels/spot and 20.190 for the promotion with all these variables partially had significant influence on the sale volume. The value of adjusted R squarewas 98% suggested that the sales volume is 98% influenced by the independent variables such as product, price, distribution channels/spot, and the promotion while the remaining 2% is influenced by other variables not examined.Â Keywords: Marketing mix, Multiple regression analysis, and Sale Volume.